Pemberantasan Terorisme dalam Kaitannya dengan Penyelundupan Obat Terlarang, Senjata dan Pencucian Uang di Kawasan Asia - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 2002)
The effor to feliminating the terrorism is notonly based to the merely law approach butit shouldbe up to the restrain of supportelement. The support elemen there means that itcould be put into action for narcotics, guns smuggling and money laundrying. Here it would there forebe eraborated the correlation among the three supporte emenfs to the effor to feiimfnating terron'sm atAsia region.